Gravitational lensing as a powerful astrophysical tool: multiple quasars, giant arcs and extrasolar planets - Wambsganß, Joachim (Annalen der Physik, 2006)
In the 25 years since the discovery of the first double quasar Q0957+561, gravitational lensing has established itself as a valuable tool in many branches of astronomy. Fields as different as galactic structure, cosmology, or extrasolar planets benefit from the gravitational lensing effect. This article starts with a brief historic reflection, then the basics of light deflection are reviewed. Observable lensing effects and a few examples of strong lensing phenomena are shown. In the main part four applications of ''strong'' lensing will be presented and discussed.